Application of Electro-Oxidation Method for Treatment of Dye Textile Wastewater Using Stainless Steel Electrode: Study of Electrolyte Concentration Effect to Color Removal - Jumardin Rua; Mega Maghfirotul Fajrin; Zaina Rohayati; Riyanto Riyanto (EKSAKTA: Journal of Sciences and Data Analysis, 2017)
The increasing number of textile industries has created a new problem of environmental pollution from waste produced. Entering of concentrated wastewater that containing of complex organic compounds to agricultural land and rivers has caused loss to humans or the environment. Treatment of dye textile wastewater by electro-oxidation method using stainless steel electrode has been done. This research consists of several stages: analysis of electrode composition with SEM-EDX, electrolysis of wastewater at variation of electrolyte concentration and analysis of electrolyte concentration effect to color removal percentage of wastewater. The result shows that the electrode composition consisted of iron, chromium, nickel and silica with the main composition of iron in the amount of 72.2%. After electrolysis on variations of electrolyte concentration and analysis of color removal percentage of wastewater, obtained that the largest of color removal percentage on the use of electrolyte concentration of 3% in the amount of 98.81%